The microarcsecond sky and cosmic turbulence - Lazio, J.; Cordes, J.; de Bruyn, A.; Macquart, Jean-Pierre (Elsevier, 2004)
Radio waves are imprinted with propagation effects from ionized media through which they pass. Owing to electron density fluctuations, compact sources (pulsars, masers, and compact extragalactic sources) can display a wide variety of scattering effects. These scattering effects, particularly interstellar scintillation, can be exploited to provide superresolution, with achievable angular resolutions ([1 las) far in excess of what can be obtained by very long baseline interferometry on terrestrial baselines. Scattering effects also provide a powerful sub-AU probe of the microphysics of the interstellar medium, potentially to spatial scales smaller than 100 km, as well as a tracer of the Galactic distribution of energy input into the interstellar medium through a variety of integrated measures. Coupled with future c-ray observations, SKA observations also may provide a means of detecting fainter compact c-ray sources. Though it is not yet clear that propagation effects due to the intergalactic medium are significant, the SKA will either detect or place stringent constraints on intergalactic scattering.